Peran Konten Akun Narasinewsroom di Platform X terhadap Literasi Politik Mahasiswa Univeristas Pendidikan Indonesia - Kayla Putri Wilfi; Cecep Darmawan; Leni Anggraeni (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This research focuses on the phenomenon of student political literacy formed through the consumption of digital content, particularly those published by the NarasiNewsroom account on the X platform (formerly Twitter). In this context, political literacy is interpreted through three main dimensions: political awareness, political knowledge, and political participation. The study employs a qualitative approach with a case study method conducted at the Universitas Pendidikan Indonesia (UPI). Data collection techniques include in-depth interviews, participatory observation, and documentation studies, which were subsequently analyzed using NVivo 15 software for qualitative data analysis. The findings reveal that NarasiNewsroom plays a significant role in shaping students’ political awareness and knowledge through information dissemination strategies that are trend-sensitive, data-driven, and communicative in nature. The content produced is effective in attracting student attention, sparking digital dialogue, and fostering critical thinking related to political issues. Nevertheless, while the content contributes to increased awareness and understanding, its influence on actual political participation remains limited. Many students remain passive, particularly in real-world political engagement outside of social media platforms. This limitation is attributed to external factors such as the academic environment’s lack of encouragement for political expression and the absence of formal political education spaces within the campus setting. Therefore, while NarasiNewsroom has proven to be a strategic digital actor in building the foundation of political literacy among the youth, the study underscores the necessity for collaborative efforts between digital media, educational institutions, and the broader social environment to cultivate a holistic and sustainable political literacy ecosystem for future generations.